Addendum to F C Eeles and R W M Clouston, ’The church and other bells of Wigtownshire’, Proceedings of the Society of Antiquaries of Scotland, 107 (1975-6) 272 - Clouston, R W M (Proceedings of the Society of Antiquaries of Scotland, 1981)
A short note with details of the Whithorn Town Steeple Bell.